Debate strategies and tactics - Paul Schutte (Communicare)
With the forthcoming second election on our doorstep, the quality of arguing and debating comes into sharp focus. This aspect has been neglected to a large extend in the past. Therefore this study gives a qualitative analysis of the Mandela versus De Klerk trend setting debate – a first for South Africa – as a step towards understanding and evaluating the processes involved in debating. In this paper the focus falls on the verbal strategies and tactics. This paper not only gives a descriptive analysis of the strategies and tactics that have been used, but where necessary, gives an evaluation of the use of them. With this information as basis, some recommendations are proposed to improve the use of strategies and tactics. These recommendations are made in the hope that it will strengthen the quality of debating in general, in order to enrich democracy and allow citizens to make well informed decisions in this year’s election.